Analisis NPL, CAR, dan NIM dalam Mempengaruhi ROA melalui BOPO pada PT. Bank Rakyat Indonesia Tbk - Silfi Oktariyani; Fauzia Nurul Fitri (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2026)
This study to analyze the effect of Non Performing Loan (NPL), Capital Adequacy Ratio (CAR), and Net Interest Margin (NIM) on Return on Assets (ROA) with Operating Expenses to Operating Income (BOPO) as an intervening variable at PT Bank Rakyat Indonesia (Perser) Tbk. This research employs a quantitative approach using secondary data obtained from the annual financial statements of Bank BRI for the period 2015-2024. The data analysis method used in this study is Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), which allows the examination of both direct and indirect relationship among variables in the research model. The independent variables consist of NPL, CAR, and NIM, the intervening variable is BOPO and the dependent variable is ROA. The results indicate that NPL has a positive effect on BOPO, suggesting that higher credit risk leads to increased operational costs. CAR and NIM have a negative effect on BOPO, indicating that adequate capital and effective interest income management improve operational efficiency contributes to increased bank profitability. The findings also confirm that BOPO mediates the relationship between NPL, CAR, and NIM on ROA. This study is expected to contribute to the academic literature on banking financial management and provide practical insights for bank management in enhancing operational efficiency and sustainable profitability.